Swimming Upstream in the Academic Library: Exploring Faculty Needs for Library Streaming Media Collections - Loftis, Elsa; Lamphere, Carly (Evidence Based Library and Information Practice, 2023)
Objective - To compare Portland State University’s (PSU) local experience of using streaming media to national and international trends identified in a large qualitative study by Ithaka S+R. This comparison will help librarians better understand if the PSU Library is meeting the needs of faculty with its streaming media collection through a series of faculty interviews.Methods and Intervention - Two librarians from PSU participated in a large, collaborative, two-part study conducted by Ithaka S+R in 2022, with 23 other academic institutions in the United States, Canada, and Germany As part of this study, the authors conducted a series of interviews with faculty from PSU’s Social Work and Film Studies departments to gather qualitative data about their use, expectations, and priorities relating to streaming media in their teaching. Ithaka S+R provided guided interview questions, and librarians at PSU conducted interviews with departmental faculty. Local interview responses were compared to the interviews from the other 23 institutions.Results - PSU Library had a higher rate of faculty satisfaction than in the larger survey. Discussions raised concerns around accessibility of content, which was novel to PSU, and did not meaningfully emerge in the broader study. Local findings did line up with broader trends in the form of concerns about cost, discoverability, and lack of diverse content.Conclusions - The data collected by Ithaka S+R’s survey, which was the first part of their two-part study, is useful as it highlights the trends and attitudes of the greater academic library community. However, the second portion of the study’s guided interviews with campus faculty reinforced the importance of accessibility, the Library’s provision of resources, and the relationships between subject liaisons and departmental instructors. It emphasized that Portland State University’s Library has built a good foundation with faculty related to this area but has not been able to provide for every streaming instructional need. Reasons for this include limited acquisitions budgets, constraints of staff time, and market factors.